Characterization of livestock herds in the lower basin of the Shanusi river Alto Amazonas – Loreto – Peru - Mathios Flores, Marco (2019)
The objective was the characterization of the milk producing cattle herds of the lower basin of the river Shanusi Alto Amazonas – Loreto – Peru. In the methodology, surveys were applied to 26 breeders, the descriptive statistics was used, for the typification, the K-means cluster analysis was applied. The quantitative variables: milk production 6,33 liters/cow, the price S/ 0,86/liter having in production 5 cows/herd, average of 14 has with improved pastures, the animal load of 1,8 AU / ha , the average labor force of 0,08 workers. Regarding the qualitative variables: 69,2% of births were from May to October, 96,2%, performed only one milking, 65,4% handled registration, 100% did not perform quality control, and 53,8% did has a milking parlor. Social – Educational, 50% of the owners carry out other agricultural activities, 42,3% of the owners have primary education and the workers 65,4%. The forage species, Brachiaria brizantha with 80,8% and 100% supplies mineral salt. Three conglomerates of extensive breeding were typified. The G1 media production with 46,15%, the G2 low production with 42,3% and G3 higher production 11,53%. The educational level of the owners makes it difficult to adopt technologies